Challenges in Early Quran Education: Identifying Factors that Affect Permata Insan Summer Camp Students' Performance - Zulkarnin Zakaria; Syazwani bt Md Sallehan; Wan Ahmad Zakry Wan Kamaruddin; Ahmad Bazli Ahmad Helmi4; Abdel Rahman Ibrahim Suleiman Islieh (Universiti Sains Islam Malaysia, 2024)
Quran education module is a major part in the PERMATA Insan Summer Camp programme for the pre-college gifted and talented students. The annual camp programme integrates STEM modules together with the Quran and Sunnah modules to help students understand and relate science topics with the Quran and Al-Sunnah. The camp participants as young as eight years old were required to memorise selected Quran verses during the camp. Many struggled to perform in the Quran education module. This study was conducted to identify various issues faced by the students in the Quran module. They were tested on their memorisation and later grouped for a special interview session. The findings on the various problems faced by them were analysed and grouped into themes. The discussion with the group of gifted and talented between the age of 8 and 11 years old revealed many concerns that have been found in earlier research on this special group of students. The findings would help further explore better ways to improve the teaching and learning of gifted and talented Muslim students.